A higher kick frequency swimming training program optimizes swim-to-cycle transition in triathlon - Ambrosini, L.; Presta, V.; Vitale, M.; Menegatti, E.; Guarnieri, A.; Bianchi, V.; De Munari, I.; Condello, G.; Gobbi, G. (The Journal of Strength and Conditioning Research, 2024)
The purpose of this study was to evaluate the effect of an 8-week swimming training program on biomechanical and physiological responses during a swim-to-cycle simulation. Fifteen triathletes were randomly allocated to 3 groups: a 6-beat-kick group (K6), a 4-beat-kick group (K4), and a control group (CG). Biomechanical and physiological parameters were evaluated during a 400-m swim and a 10-minute cycle segment before (Pretraining) and after (Posttraining) the program. A lower stroke frequency (p = 0.004) and a higher stroke length (p = 0.002) was found in K6 compared with CG at Posttraining. A reduction in the K6 emerged between Pretraining and Posttraining during cycling for heart rate (p = 0.005), V?O2 (p = 0.014), and energy expenditure (p = 0.008). A positive association emerged between swim kick index and cycling cadence in the K6 group. The improvement in stroke frequency and length observed in the K6 group could be explained as an improvement in swimming technique. Similarly, the reduction in energy expenditure during cycling at Posttraining for the K6 group suggests an improvement in the working economy. Triathlon coaches and athletes should consider the inclusion of high swim kick into their training programs to enhance swim and cycling performance, which can ultimately lead to an improvement in the swim-to-cycle transition and the overall triathlon performance.